2018
DOI: 10.1007/s12020-018-1701-6
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the relationship between thyroid nodule characteristics, insulin resistance and arterial stiffness in euthyroid nodular goiter

Abstract: We found that PWV was significantly higher in patients with euthyroid nodular goiter. This result suggests that these patients may be at risk for cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…There were also differences between the groups in terms of HOMA-IR and insulin level. HOMA-IR did not correlate with thyroid volume, nodule volume and nodule count 30 . While a prospective study not found difference in thyroid volume or the presence of nodular thyroid diseases among the groups with presence or absence of insulin resistance.…”
Section: Discussionmentioning
confidence: 71%
“…There were also differences between the groups in terms of HOMA-IR and insulin level. HOMA-IR did not correlate with thyroid volume, nodule volume and nodule count 30 . While a prospective study not found difference in thyroid volume or the presence of nodular thyroid diseases among the groups with presence or absence of insulin resistance.…”
Section: Discussionmentioning
confidence: 71%
“…In terms of insulin resistance [IR] evaluation, most of the prior studies evaluated IR using HOMA-IR [19] .…”
Section: Discussionmentioning
confidence: 99%
“…We preferred arterial stiffness measurement to detect cardiovascular risk in the patients with hypoparathyroidism. Since validity and reliability of this method was shown in many studies, we also used it to detect cardiovascular risk in some endocrinological diseases in our previous studies (32)(33)(34)(35). Increase of the experiences and researches on this topic shows that arterial stiffness method which is easy and noninvasive to implement shall gradually enter into medical practice routine.…”
Section: Discussionmentioning
confidence: 99%